Quasi-Exact Solvability of a Hyperbolic Intermolecular Potential Induced by an Effective Mass Step - Axel Schulze-Halberg (International Journal of Mathematics and Mathematical Sciences)
It is shown that a nonsolvable third-order hyperbolic potential becomes quasi-exactly solvable after the introduction of a hyperbolic effective mass step. Stationary energies and L2-solutions of the corresponding Schrödinger equation are obtained in explicit form.